The Influence of Principal Managerial Competence and Work Motivation on Teacher Professionalism of Vocational High Schools - Habibi, Beni (Dinamika Pendidikan, 2015)
This research aims to analyze the influence of principal managerial competence, working motivation on teacher professionalism. This research employs a non-experimental quantitative approach. The population was 172 teachers at Business and Management Vocational High Schools in Tegal. 114 teachers were analyzed as sample and data were collected by using questionnaire. Findings show that the principal managerial competence and work motivation have significant influence on teacher professionalism.. The influence of those two variables on teacher professionalism is 47.8%. Based on the regression analysis, it shows that there is a positive and significant influence of principal managerial competence on teacher professionalism, which is equal by 17.7%. Working motivation has also positive and significant influences on teacher professionalism with the coefficient of determination by 46.8%. Furthermore, the result of multiple regression analysis shows that the influence of both variables simultaneously influence on teacher professionalism with the coefficient of determination by 47.8%.Â